Gospel Genealogies and Jesus’s Jewishness - Sievers, Joseph (Studies in Christian-Jewish Relations, 2026)
Nostra Aetate considers the spiritual bond between Christians and Jews as part of the mystery of the church and of its very identity. The New Testament presents this intimate connectedness concretely, starting with the genealogies of Jesus in the Gospels of Matthew and Luke and culminating with the inscription on the cross that is found in various forms in all four canonical gospels but always containing the words “the king of the Jews/Judeans.” In Matthew, Jesus’s genealogy was the first basis for the assertion of his Jewishness, which this essay will study in detail. The evangelist wants his readers to understand that Jesus’s lineage and identity is rooted in Abraham himself, the “founding Father” of the Israelite and Jewish people. This presentation of Jesus’s ancestry may not always be appreciated in today’s discussion of his Jewishness. Yet, there is no clearer indication of his rootedness in the Jewish people than the Matthean genealogy.